Income Inequality, Mobility and the Accumulation of Capital - Cecilia García-Pe\~nalosa; Stephen J. Turnovsky (Center for Economic Studies and ifo Institute (CESifo), 2013)
We examine the determinants of income mobility and inequality in a Ramsey model with elastic labor supply and heterogeneous wealth and ability (labor endowment). Both agents with lower wealth and with greater ability tend to supply more labor, implying that labor supply decisions may have an equalizing or unequalizing effect depending on the relative importance of the two sources of heterogeneity. Moreover, these decisions are central to the extent of mobility observed in an economy. The relationship between mobility and inequality is complex. For example, a reduction in the interest rate and an increase in the wage rate reduce capital income inequality and allow upward mobility of the ability-rich. However, the increase in the labor supply of high ability agents in response to higher wages raises earnings dispersion and thus has an offsetting effect. As a result, high mobility can be associated with an increase or a decrease in overall income inequality.
Keywords: D31; O41; 330; inequality; income mobility; endogenous labor supply; transitional dynamics